(untitled) (Journal of Dhaka Medical College, 2011)
Objective: This study aims to describe main perpetrator of violence area and prevention of violence against women. Study design: A cross sectional study was carried out in One-stop Crisis Centre (OCC) of Dhaka Medical College Hospital, Dhaka, Bangladesh during the period of June 2006 to May 2007. Methods: 284 victims reported in OCC during the study period were selected as cases for the study and quantitative information was collected from them using cross sectional for the present study. Results: Study shows that most of the violence is done by husband (46.48%) and prevalence is more in rural areas (80.98%) in comparison to urban area (19.02%). Physical assault is the most common type of violence (50.35%), followed by sexual assault (36.63%) and burn (13.02%) Housewives are tortured more (67%). Conclusion: Proper implementation of existing rules and community based interventions for raising awareness about the domestic violence against women are recommended. Key words: Violence against women; assault; human rights; one-stop crisis centre (OCC); Bangladesh. DOI: 10.3329/jdmc.v19i2.7077 J Dhaka Med Coll. 2010; 19(2) : 98-101